An End-to-End Model Reveals Losers and Winners in a Warming Mediterranean Sea - Moullec, Fabien; Barrier, Nicolas; Drira, Sabrine; Guilhaumon, François; Marsaleix, Patrick; Somot, Samuel; Ulses, Caroline; Velez, Laure; Shin, Yunne-Jai (Frontiers in Marine Science, 2019)
The Mediterranean Sea is now recognized as a hotspot of global change, ranking among the fastest warming ocean regions. In order to project future plausible scenarios of marine biodiversity at the scale of the whole Mediterranean basin, the current challenge is to develop an explicit representation of the multispecies spatial dynamics under the combined influence of fishing pressure and climate change. Notwithstanding the advanced state-of-the-art modelling of food webs in the region, no previous studies have projected the consequences of climate change on marine ecosystems in an integrated way, considering changes in ocean dynamics, in phyto- and zoo-plankton productions, shifts in Mediterranean species distributions and their trophic interactions at the whole basin scale. We used an integrated modelling chain including a high-resolution regional climate model, a regional biogeochemistry model and a food web model OSMOSE to project the potential effects of climate change on biomass and catches for a wide array of species in the Mediterranean Sea. We showed that projected climate change would have large consequences for marine biodiversity by the end of the 21st century under a business-as-usual scenario (RCP8.5 with current fishing mortality). The total biomass of high trophic level species (fish and macroinvertebrates) is projected to increase by 5% and 22% while total catch is projected to increase by 0.3% and 7% by 2021-2050 and 2071-2100, respectively. However, these global increases masked strong spatial and inter-species contrasts. The bulk of increase in catch and biomass would be located in the southeastern part of the basin while total catch could decrease by up to 23% in the western part. Winner species would mainly belong to the pelagic group, are thermophilic and/or exotic, of smaller size and of low trophic level while loser species are generally large-sized, some of them of great commercial interest, and could suffer from a spatial mismatch with potential prey subsequent to a contraction or shift of their geographic range. Given the already poor conditions of exploited resources, our results suggest the need for fisheries management to adapt to future changes and to incorporate climate change impacts in future management strategy evaluation.